2017
DOI: 10.1089/thy.2016.0199
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of the Thr92Ala Polymorphism of Deiodinase-2 on Thyroid Hormone Parameters, Health-Related Quality of Life, and Cognitive Functioning in a Large Population-Based Cohort Study

Abstract: The Thr92Ala polymorphism of D2 was not associated with thyroid parameters, HRQoL, and cognitive functioning in the general population and in participants on thyroid hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 46 publications
2
68
2
Order By: Relevance
“…Almost all studies have shown identical serum TSH and thyroid hormone concentrations in hypothyroid patients harbouring different DIO2 polymorphism in rs225014 [17, 25-37] and rs12885300 [27, 28, 30]. However, a few exceptions have also been published [25, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies have shown identical serum TSH and thyroid hormone concentrations in hypothyroid patients harbouring different DIO2 polymorphism in rs225014 [17, 25-37] and rs12885300 [27, 28, 30]. However, a few exceptions have also been published [25, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of such an association in another study might be due to a smaller sample size (20). A recent large populationbased cohort study did not find an association between Thr92Ala and outcomes of T4 therapy such as quality of life and cognitive functioning (23). SNPs in the brain-specific thyroid hormone transporter OATP1C1 (also known as SLCO1C1) are associated with fatigue and depression in T4-treated patients, but not with neurocognitive test results or a preference for combination therapy (35).…”
Section: Introductionmentioning
confidence: 91%
“…The most studied variant is rs225014 (Thr92Ala), which also had no effects on serum TSH, FT4 or T3 (20,21) but interestingly has been associated with diabetes, psychological well-being, hypertension and the risk of osteoarthritis (22). A recent large study reports the presence of DIO2 Thr92Ala in 10.7% of the general population and in 11.3% of T4 users (23). In neither group was the polymorphism associated with differences in serum TSH, FT3, FT4, FT3/FT4 ratio, quality of life or cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, in which participants taking LT4 were recruited by letter and then completed questionnaires assessing well-being, also showed lower scores in 2 different questionnaires in the euthyroid patients taking L-T4, although the comparison was with standard reference values, rather than a matched control group (8). In several more recent studies, treated female patients with hypothyroidism were found to have worse quality of life compared with control groups using the RAND-36 Short Form Survey Instrument (SF-36) (9), the ThyPRO and SF-36 questionnaires (10), the SF-36, the Hospital Anxiety and Depression Scale, and the multidimensional fatigue inventory questionnaire (11), and worse mental health using the General Health Questionnaire (GHQ) (12). One of these studies, which examined patients before and after initiation of LT4, showed improvement in some ThyPRO and SF-36 subscales as serum TSH was normalized from a median of 8.1 to 2.6 mIU/L.…”
Section: Patient-reported Outcomes During Levothyroxine Therapymentioning
confidence: 99%